2011
DOI: 10.1111/j.1948-7134.2011.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition habitat selection by Anopheles gambiae in response to chemical cues by Notonecta maculata

Abstract: A number of mosquito species avoid predator-inhabited oviposition sites by detecting predator-released kairomones. In the laboratory, we found that when offered de-ionized water and de-ionized water conditioned with Notonecta maculata, gravid Anopheles gambiae females preferentially oviposited into the former. We then conducted further experiments using two chemical components found in Notonecta-conditioned water, chemically pure n-tricosane and/or n-heneicosane, that was previously shown to repel oviposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Mutero et al () demonstrated that ammonium sulphate fertilizer increased Anopheles arabiensis oviposition, based on the fact that gravid females use visual and olfactory stimuli to select habitats for oviposition (Bentley and Day ). This suggests that Anopheles gambiae actively selects habitats for oviposition rather than randomly (Minakawa et al ) and can avoid predator‐released kairomones of Notonecta (Warburg et al ). In our mesocosms, flash flood disturbance may have removed mosquito food resources besides mosquito antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Mutero et al () demonstrated that ammonium sulphate fertilizer increased Anopheles arabiensis oviposition, based on the fact that gravid females use visual and olfactory stimuli to select habitats for oviposition (Bentley and Day ). This suggests that Anopheles gambiae actively selects habitats for oviposition rather than randomly (Minakawa et al ) and can avoid predator‐released kairomones of Notonecta (Warburg et al ). In our mesocosms, flash flood disturbance may have removed mosquito food resources besides mosquito antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…An example of an effect of predator presence on mosquito oviposition is seen in Culiseta longiareolata (Macquart), which has been shown to respond negatively to hydrocarbons released by hemipteran predators (Silberbush et al 2010). A similar response to the same hemipteran predator was seen in Anopheles gambiae (Giles) females, though this was apparently not mediated by hydrocarbons (Warburg et al 2011). …”
mentioning
confidence: 69%
“…Oviposition is primarily driven by female preferences based on cues of habitat suitability (Reiskind and Wilson 2004), and occurs in response to the physical and chemical stimuli that characterize a habitat (Bentley and Day 1989). Apart from perceiving the physical properties of the habitat (e.g., size, shape), certain mosquito species have been demonstrated as having the ability to detect signals from aquatic habitats that indicate the presence of conspecifics, predatory threats to larvae, and the availability of larval food resources, though responses to these signals are largely dependent upon the individual species in question (Edgerly et al 1998, Reiskind and Wilson 2004, Silberbush et al 2010, Warburg et al 2011). In one study, response of Ae.…”
mentioning
confidence: 99%
“…Ovipositing Culicidae, e.g., Culiseta (Allotheobaldia) longiareolata (Macquart, 1838), Culex (Culex) laticinctus (Edwards, 1913), and Anopheles gambiae (Giles, 1902), avoid predator-rich water bodies because they are able to detect predatorreleased kairomones. In fact, the active avoidance of water bodies with a high abundance of predators such as Notonecta maculata Fabricius, 1794 can strongly support a mosquito population (Warburg et al 2011). …”
Section: Predatorsmentioning
confidence: 98%